Graphene-Pt\ITO counter electrode to significantly reduce Pt loading and enhance charge transfer for high performance dye-sensitized solar cell - Guai, Guan Hong (2013)
A graphene-Pt\ITO (ITO-PG) counter electrode is fabricated by electrochemical deposition of a porous graphene film on a low-loaded Pt\ITO electrode. Compared to both plain graphene and Pt films, the graphene-coated Pt composite film provides large and superior conductive interface for significant improvement of Pt utilization efficiency and charge transfer, which in turn leads to higher power conversion efficiency of the dye-sensitized solar cell (DSSC). As compared to conventional Pt-coated counter electrode, the Pt loading of ITO-PG electrode can be reduced by more than 60% to 1.9 μg cm−2 while achieving even better performance. The performance enhancement mechanism is proposed. This work renders an economical manufacturing process to fabricate high performance DSSC for potential commercial production.